Basal encephalocele associated with morning glory syndrome: case report Encefalocele basal associada a síndrome "morning glory": relato de caso - Ivanete Minotto; Nitamar Abdala; Adriana Aparecida Siviero Miachon; Angela Maria Spinola e Castro; Paulo Imamura; Roberto Gomes Nogueira (Arquivos de Neuro-Psiquiatria)
The basal encephaloceles refer to rare entities and they correspond to herniation of brain tissue through defects of skull along the cribiform plate or the sphenoid bone. A rare morning glory syndrome, with characteristic retinal defect has been reported in association with basal encephaloceles. Hypophysis hormonal deficiencies may occur. We accounted for a pituitary dwarfism with delayed diagnosed transsphenoidal encephalocele associated with morning glory syndrome, showing the alterations found in retinography, computed tomography and magnetic resonance imaging. As encefaloceles basais são entidades raras e correspondem a herniações do tecido cerebral através de um defeito do crânio, ao longo da lâmina crivosa etmoidal ou do osso esfenoidal. A rara síndrome morning glory, com alterações de fundo de olho características pode apresentar-se associada à encefalocele basal. Deficiências hormonais hipofisárias podem ocorrer. Relatamos caso de nanismo hipofisário com encefalocele transesfenoidal de diagnóstico tardio associada à síndrome de morning glory, mostrando as alterações na retinografia, tomografia computadorizada e ressonância magnética.